Analysis of secondary metabolite compounds from leaves extract kesambi (Schleichera oleosa) and antioxidant activity test - Boima Situmeang; Weny Nuraeni; Agus Malik Ibrahim; Saronom Silaban (Pascasarjana Universitas Negeri Medan, 2016)
Abstract. Kesambi (Schleichera oleosa) is one of plants that have the potential to treat various deasease. Kesambi plant or kusum widely spread in Asia such as India, Nepal, Malaysia and Indonesia. In Indonesia, this plant widely available in Java precisely Cilegon and Jember area. This study aimed to analyze the content of secondary metabolites from plants kesambi extract and antioxidant activity test of hexane, ethyl acetate and water fraction. Analysis of secondary metabolites is done with phytochemical and GC-MS test methods. Extraction was done by using maceration and fractionation methods. Antioxidan tactivity test using DPPH methods. The content of secondary metabolites contained in leaves kesambi (Schleichera oleosa) are flavonoids, alkaloids, tannins, phenols, and steroids. Based on IC50 values were obtained from three fraction, ethyl acetate fraction had a strong radical inhibition rate than the fraction of water and n-hexane. IC50 fraction of ethyl acetate, water, and n-hexane successively are: 206.0851; 272.2891 and 425,1143 ppm respectively. Keyword: kesambi, schleichera oleosa, DPPH, antioxidant